2023
DOI: 10.1186/s12913-023-09985-5
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for an economic evaluation of a tele-neurologic intervention alongside a stepped wedge randomised controlled trial (NeTKoH)

Ana S. Oliveira Gonçalves,
Imke Mayer,
Ricarda S. Schulz
et al.

Abstract: Background A significant and growing portion of the global burden of diseases is caused by neurological disorders. Tele-neurology has the potential to improve access to health care services and the quality of care, particularly in rural and underserved areas. The economic evaluation of the stepped wedge randomised controlled trial NeTKoH aims to ascertain the cost-effectiveness and cost-utility regarding the effects of a tele-neurologic intervention in primary care in a rural area in Germany. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…To explore the decision uncertainty associated with the cost-effectiveness of iFraP to enhance bisphosphonate adherence we will conduct a VoI analysis. An electronic search of trial-based economic evaluation of digital health interventions study protocols identified only three study protocols and neither of these included a trial based VoI analysis [42][43][44] . No VoI analysis was found when searching the published literature for protocols of cost-effectiveness analyses of digital support tools.…”
Section: Strengthsmentioning
confidence: 99%
“…To explore the decision uncertainty associated with the cost-effectiveness of iFraP to enhance bisphosphonate adherence we will conduct a VoI analysis. An electronic search of trial-based economic evaluation of digital health interventions study protocols identified only three study protocols and neither of these included a trial based VoI analysis [42][43][44] . No VoI analysis was found when searching the published literature for protocols of cost-effectiveness analyses of digital support tools.…”
Section: Strengthsmentioning
confidence: 99%